2017
DOI: 10.4315/0362-028x.jfp-17-108
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Consumer Food Safety Practices and Knowledge: Foodbook Study

Abstract: Understanding consumers' food safety practices and knowledge supports food safety education for the prevention of foodborne illness. The objective of this study was to describe Canadian consumer food safety practices and knowledge. This study identifies demographic groups for targeted food safety education messaging and establishes a baseline measurement to assess the effectiveness of food safety interventions over time. Questions regarding consumer food safety practices and knowledge were included in a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 17 publications
3
48
2
8
Order By: Relevance
“…Although 116 consumers indicated that they knew how they could protect themselves, 36.2% (42/116) did not know that transmission occurs via meat. In general, consumers are aware that food-borne infections are often associated with chicken meat [34,35], but an international comparison also shows that consumers do not know that meat is a vector of Campylobacter. An Australian study showed that only 9% of consumers associate Campylobacter with chicken and poultry [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 116 consumers indicated that they knew how they could protect themselves, 36.2% (42/116) did not know that transmission occurs via meat. In general, consumers are aware that food-borne infections are often associated with chicken meat [34,35], but an international comparison also shows that consumers do not know that meat is a vector of Campylobacter. An Australian study showed that only 9% of consumers associate Campylobacter with chicken and poultry [16].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of students at the University of Maine showed that slightly more than half of those surveyed (57.3%) were aware of an association between Salmonella and raw chicken [38]. Murray and Glass-Kaastra [34] showed that the majority of respondents are aware of the risks of foodborne illness associated with chickens, and the majority are aware that chickens that are not fully cooked can be a cause of foodborne illness. A study in Mexico showed that fresh meat is the most commonly considered sources of salmonellosis compared to other food categories, such as "fruits and vegetables" or "dairy products" [39].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of the survey respondents indicated the use of the same cutting board and knife when handling different food products, whereas almost 40% reported washing them with soap and water (Table ). Other studies have found washing percentages of 19.7% to 67.1% when raw meat is used prior to RTE products (Garayoa et al., ; Mitakakis et al., ; Murray et al., ).…”
Section: Resultsmentioning
confidence: 95%
“…The age group between 60 and 64 years old reported to have the least hand washing frequency. Other studies have also reported that these population groups (men, young, and elder consumers) have the most unsafe food handling practices (Garayoa et al., ; Murray et al., ; Patil, Morales, Cates, Anderson, & Kendall, ; Roseman & Kurzynske, ; RĂžssvoll et al., ).…”
Section: Resultsmentioning
confidence: 96%
“…Food security and control are, therefore, matters of great preoccupation for consumers. Consumer reliability on frozen and chilled food, especially related to aspects of the supply chain, is of high priority for all involved in the production, commercialization, logistics and distribution of foods (Galarz et al, 2010;Murray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%